2010
DOI: 10.1016/j.respol.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Government R&D subsidies as a signal for private investors

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
147
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(169 citation statements)
references
References 29 publications
9
147
0
13
Order By: Relevance
“…本文的研究变量有两项:政府研发资助和国家科研机构创新产出。关于前者,本文参考 Brown [5] 、Kleer [6] 、梁莱歆 [9] 等人的做法,采用国家科研机构研发经费内部支出中来源自政 府资金的部分作为相应的测度指标,并对其流量数据(GInsRD)取对数(LNGInsRD);关 于后者,本文借鉴王俊 [16] 、Mario [17] [17] 、Paul [21] 等人研究得出的结论一致,本文的研究结果显示,政府研发资金能够提升 国家科研机构的创新产出,从而证实了对于公共科研机构而言政府研发资助具有激励效应和 产出效率。政府研发资助对国家科研机构创新产出的促进作用主要依靠两种路径来实现 [22,23] :一是对科研人员物质需求的满足,使科研人员的工作积极性和满意度大幅提高,从而 形成对其研发活动效率的正向激励作用;二是对技术设备的更新、改造和升级,使科研机构 …”
Section: .研究设计unclassified
See 1 more Smart Citation
“…本文的研究变量有两项:政府研发资助和国家科研机构创新产出。关于前者,本文参考 Brown [5] 、Kleer [6] 、梁莱歆 [9] 等人的做法,采用国家科研机构研发经费内部支出中来源自政 府资金的部分作为相应的测度指标,并对其流量数据(GInsRD)取对数(LNGInsRD);关 于后者,本文借鉴王俊 [16] 、Mario [17] [17] 、Paul [21] 等人研究得出的结论一致,本文的研究结果显示,政府研发资金能够提升 国家科研机构的创新产出,从而证实了对于公共科研机构而言政府研发资助具有激励效应和 产出效率。政府研发资助对国家科研机构创新产出的促进作用主要依靠两种路径来实现 [22,23] :一是对科研人员物质需求的满足,使科研人员的工作积极性和满意度大幅提高,从而 形成对其研发活动效率的正向激励作用;二是对技术设备的更新、改造和升级,使科研机构 …”
Section: .研究设计unclassified
“…The empirical results indicate that a long-term, stable and equilibrium relation exists between government's R&D funding and public R&D institutes' invention patent authorization, and furthermore the contribution from government's R&D funding to public R&D institutes' invention patent authorization is also significant in a short term; From the view of annual variation, the government's R&D funding is the Granger cause of public R&D institutes' granted invention patents, while the patents are not the Granger cause of government's R&D funding; As a practical conclusion, the government's R&D funding could expectedly improve innovation output of public R&D institutes in China. [2] 。政府研发资助的主要功能就 是通过降低技术创新成本从而有效缩小技术创新的私人边际收益率与社会边际收益率的差 距,以维持资助对象的研发动力 [3] 。这一理论对于政府研发资助偏向于具有广泛技术溢出效 应的项目或组织而言具有积极意义。但是,该理论认为政府研发资助对私人投资存在替代效 应,且没有充分考虑到专利保护对知识溢出的限制作用,因而难以解释一些行业内部组织为 追求终身垄断专利而开展的研发投资行为。(2)融资约束松绑理论。该理论认为,源于信息 不对称的逆向选择和道德风险决定了研发融资的困难性,造成社会研发投入不足 [4] [5] 。政府 研发资助可以弥补这一短板,一方面直接缓解研发资金的社会需求,另一方面能分担研发活 动的高风险,从而降低研发项目或组织的融资约束。该理论指出了政府研发资助对市场投资 人的激励效应,而且强调了社会创新主体的研发成果对于政府资助行为取向的重要性。(3) 信号功能传递理论。该理论认为,政府研发资助发挥了鉴别研发项目或组织是否具备技术优 势和质量的重要作用,市场投资人根据政府行为决定是否对研发项目或组织给予资金支持 [6] [7] 。该理论将政府研发资助视作中介变量,重点研究市场投资人、政府、研发主体的三方 博弈关系,但可能夸大了政府的甄别能力而忽视了如何激励政府选择出最优项目这一问题。 近年来,一些研究人员对中国的政府研发资助进行了探讨。舒红娟对中国的政府研发资 助规模和效果开展了评价研究,指出国内的政府研发资助效果仍有改善的空间 [8] 。周海涛、 张振刚通过实证研究发现,作为国内政府研发资助的两种重要方式,经费补助比税收优惠具 有更大的创新激励作用 [9] 。朱斌认为,国内的政府研发资助具有一定的对象偏向性,要提高 政府研发资助的效率可从事前评估、事中监督和事后激励着手 [10] 。白俊红、卞元超指出,区 域基础设施环境、人力资本环境、金融环境以及制度环境对政府研发资助均具有显著的正面 促进作用,但经济发展环境的影响效应并不显著 [11] 。 总体而言,上述研究主要考察政府研发资助与企业创新的关系,而鲜有探讨政府研发资 助对科研机构、高校等其它创新主体的影响作用。而相关实证研究的结论则表明,政府研发 资助不一定促进企业创新产出 [12,13,14,15,16] 。这种不确定性对于科研机构而言是否同样存在? 中国政府研发资助能否提高国家科研机构的创新产出?基于此,本文以国家科研机构作为研 究对象,围绕中国政府研发资助的效果问题,通过协整分析、建立误差修正模型以及格兰杰 因果关系检验,实证考察政府研发资助和国家科研机构创新产出之间的长期及短期关系。…”
unclassified
“…However, government intervention may well cause more problems than it solves… It is therefore unclear whether government supply of these services enhances welfare." Takalo and Tanayama (2010), and Kleer (2010) focused on the adverse selection problems in the framework of theoretical models, and concluded that state subsidy may help to resolve this kind of market failure. On the other hand, Chaney and Thakor (1985) examined the moral hazard and demonstrated that loan guarantees provided by the state create perverse incentives for the firms.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kleer (2010), government subsidies for research and development (R&D) could be intended to promote projects with high returns to society but too little private returns to be beneficial for private investors. They applied a simple signaling model with different kinds of R&D projects to capture this phenomenon.…”
Section: Introductionmentioning
confidence: 99%